Occluded mammary graft post-coronary bypass surgery: do we need to look for the second one? A case report. Issue 2 (7th June 2019) - Yalonetsky, Sergey; Roguin, Ariel; Gross, Gil; Beyar, Rafael
Abstract: Background: Anatomic variations of the left internal mammary artery (LIMA) can influence coronary artery bypass surgical technique as well as posing definite difficulties in the interpretation of angiographic findings. We present an unusual anatomic variant of two LIMAs originating from the left subclavian artery discovered post-coronary artery bypass grafting surgery. Case summary: A 60-year-old man post-LIMA grafting of the left anterior descending (LAD) coronary artery underwent diagnostic cardiac catheterization. Selective angiography revealed occluded LIMA; therefore, it was decided to proceed with percutaneous coronary intervention (PCI) to the occluded native LAD. Once antegrade flow in the LAD was restored, retrograde filling of a vessel corresponding to the previously grafted LIMA was also detected. Additional contrast injection in the left subclavian artery (LSCA) showed a second patent LIMA originating from the distal segment of the LSCA. Discussion: This patient has an unusual anatomic variant of two LIMAs originating from the LCSA. The proximal rudimentary LIMA was misinterpreted as an occluded arterial graft while the second, well-developed LIMA connected to the LAD had an unusually distal origin and had therefore been overlooked. This anatomical variant should be kept in mind when the internal mammary graft seems to be occluded.